2016
DOI: 10.3390/ijms18010047
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Trafficking of Mammalian Lysosomal Proteins: An Extended View

Abstract: Lysosomes clear macromolecules, maintain nutrient and cholesterol homeostasis, participate in tissue repair, and in many other cellular functions. To assume these tasks, lysosomes rely on their large arsenal of acid hydrolases, transmembrane proteins and membrane-associated proteins. It is therefore imperative that, post-synthesis, these proteins are specifically recognized as lysosomal components and are correctly sorted to this organelle through the endosomes. Lysosomal transmembrane proteins contain consens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 175 publications
1
77
0
3
Order By: Relevance
“…6A). When we ran the same diC8-PI(3,4,5)P 3 concentration curves in the presence of 10 µM cpd541 and 10 µM cpd984, we found that cpd541 abolished PI(3,4,5)P 3 We previously showed that circulating VLDL contains more PI(3,4,5)P 3 than LDL 17 . Using these same fractions, we characterized rat derived circulating VLDL and LDL binding to Sortilin using SPR and MST.…”
Section: Characterization Of Vldl and Ldl Sortilin Affinitymentioning
confidence: 68%
See 1 more Smart Citation
“…6A). When we ran the same diC8-PI(3,4,5)P 3 concentration curves in the presence of 10 µM cpd541 and 10 µM cpd984, we found that cpd541 abolished PI(3,4,5)P 3 We previously showed that circulating VLDL contains more PI(3,4,5)P 3 than LDL 17 . Using these same fractions, we characterized rat derived circulating VLDL and LDL binding to Sortilin using SPR and MST.…”
Section: Characterization Of Vldl and Ldl Sortilin Affinitymentioning
confidence: 68%
“…Vps10 orthologue Sortilin in mammals traffics proteins from the Golgi where it is activated by furin mediated cleavage of its prodomain 2 . Sortilin is responsible for trafficking its ligands between secretory pathways and lysosomal protein pathways 3 . Vps10 and its mammalian counterpart Sortilin release cargo upon entering acidic endosomal compartments, which may be followed by dimerization of the luminal b-propeller domains of Sortilin.…”
Section: Introductionmentioning
confidence: 99%
“…We then scanned the C-terminal of TMEM127 for potential tyrosine-based motifs (YXXΦ), where X is any amino acid and Φ is a bulky, hydrophobic acid (F,I,L,M or V), and [34][35][36] . Although these are considered to be the two classical motifs, as signaling motifs can be diverse, we also considered other less common variations such as extended-acidic, dileucine-based, endocytic motifs [37][38][39][40][41] .…”
Section: Identification Of Mechanisms Governing Tmem127 Internalizatimentioning
confidence: 99%
“…The presence of various sorting signals is essential for recruiting the sorting machinery, beginning with the mono‐ubiquitination of single or multiple lysine residues on the receptor tyrosine kinases (RTKs) (Jovic et al , ). Tyrosine and di‐leucine motifs are required for clathrin‐mediated transport from vesicles to endosomes and lysosomes (Staudt, Puissant & Boonen, ). Two microdomains of early endosomes, including the tubular endosomal network (TEN) and vacuolar domain, contribute towards the sorting process.…”
Section: Overview Of the Endocytic Pathwaymentioning
confidence: 99%
“…The transmembrane proteins involved in endocytic pathways are synthesized in the ER, and may either be directly sorted from the TGN to the endosomes or sorted to the cell surface from which they associate with endocytic pathways. Classical endosomal sorting is mostly dependent on clathrin‐coated vesicles (CCVs) (Robinson, ; Staudt et al , ). Clathrin has a pivotal role in many cellular processes such as endosomal sorting complex required for transport (ESCRT)‐dependent cargo sorting to endosomes, mitosis, and secretory protein transport from the TGN (McMahon & Boucrot, ).…”
Section: The Interplay Of Conventional and Non‐conventional Pathways mentioning
confidence: 99%